1992
DOI: 10.1002/bit.260401010
|View full text |Cite
|
Sign up to set email alerts
|

Kinetic studies on urea hydrolysis by immobilized urease in a batch squeezer and flow reactor

Abstract: The immobilization of urease on the reticulated polyurethane foam, and the kinetic phenomenon of urea hydrolysis by the resulting immobilized urease in both batch squeezer and circulated flow reactors were studied. Urease was immobilized with bovine serum albumin and glutaraldehyde on polyurethane foam support of 7 to 15 mum thickness. The residual apparent activity of urease after immobilization was about 50%. The good hydrodynamic property and flexibility of polyurethane foam were retained in solution after … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

1995
1995
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(3 citation statements)
references
References 19 publications
0
3
0
Order By: Relevance
“…The enzymatic activity retained by the magnetic particles is appraised by injecting substrate (urea) to the main channel. Urea is hydrolyzed by the enzyme according to the reaction and, if a buffering system formed by NH 3 and NH 4 + is considered, the pH in the injection zone will vary according to pH = p K a + log([NH 3 ]/[NH 4 + ]). If [NH 4 + ] is kept constant in the carrier channel and at a value higher than [NH 3 ], then the enzyme reaction will produce a rise of pH that will be a linear function of log[NH 3 ].…”
Section: Resultsmentioning
confidence: 99%
“…The enzymatic activity retained by the magnetic particles is appraised by injecting substrate (urea) to the main channel. Urea is hydrolyzed by the enzyme according to the reaction and, if a buffering system formed by NH 3 and NH 4 + is considered, the pH in the injection zone will vary according to pH = p K a + log([NH 3 ]/[NH 4 + ]). If [NH 4 + ] is kept constant in the carrier channel and at a value higher than [NH 3 ], then the enzyme reaction will produce a rise of pH that will be a linear function of log[NH 3 ].…”
Section: Resultsmentioning
confidence: 99%
“…2) show that the mem- EPOXY-DERIVED pHEMA MEMBRANE brane has a highly open pore structure, which may lead to high internal surface area (implying high immobilization capacity). 4,[12][13][14][15]25,26 Analysis of wash solutions showed that the immobilization process was irreversible.…”
Section: Immobilization Of Urease and Kinetic Constantsmentioning
confidence: 99%
“…Immobilized microorganism and enzyme offer a considerable reduction in BOD and COD level facilitating a continuous operation [2][3]. But immobilized enzyme technology, to become commercially viable in industrial applications, parameters such as cost of getting purified enzyme, carrier matrix and coupling techniques are some of the important factors to be considered in detail [3][4][5][6].…”
Section: Introductionmentioning
confidence: 99%